2008
DOI: 10.1002/pc.20610
|View full text |Cite
|
Sign up to set email alerts
|

Tensile properties of LDPE + Boehmite composites

Abstract: Effect of interfacial interactions on mechanical properties of composites of low‐density polyethylene reinforced with micrometric Boehmite powders were studied in combination with two silane coupling agents vinyltri(2‐methoxyethoxy)‐silane (VTMES)‐SCA 972 and 3‐(trimethoxysilyl)‐propylmethacrylate (3MPS)‐SCA 989. Samples were prepared via melt mixing followed by compression or injection molding. Morphology and mechanical behavior of the composites were investigated as a function of the filler loading. The modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Similar finding was recently reported on the BA dispersion in poly('-caprolactone) [34]. As already observed by Brostow et al [35], although the dispersion is not affected by the surface treatment of BA nanoparticles, a better polymer-filler interaction takes place due to replacement of hydroxide surface groups of the nanoparticles with organic ones. The hypothesis of an improved adhesion is consistent with the increment of the mechanical performance as reported later.…”
Section: Mechanical Testssupporting
confidence: 75%
“…Similar finding was recently reported on the BA dispersion in poly('-caprolactone) [34]. As already observed by Brostow et al [35], although the dispersion is not affected by the surface treatment of BA nanoparticles, a better polymer-filler interaction takes place due to replacement of hydroxide surface groups of the nanoparticles with organic ones. The hypothesis of an improved adhesion is consistent with the increment of the mechanical performance as reported later.…”
Section: Mechanical Testssupporting
confidence: 75%
“…Furthermore, a better polymer-filler adhesion occurred due to replacement of hydroxide groups on the surface of the nanoparticles with organic groups (Brostow et al, 2009), showing a lot less cavities due to detachment of aggregates and agglomerates. A similar filler dispersion is recognizable in the case of BA nanoparticles surface treated with benzene-sulfonic acid (carrying apolar tails), probably because of the higher hydrophobicity of the BA which indicates a lower tendency to filler aggregation ( Figure 1c) (Adhikari et al, 2012).…”
Section: Morphologymentioning
confidence: 99%
“…These results suggest that the utilization of surface-treated BA is essential to achieve higher strength and stiffness at low nanofiller concentrations. Brostow et al studied the tensile properties and properties at the interface of low density polyethylene (LDPE) filled with untreated and silane functionalized BA nanoparticles (Brostow et al, 2009). In his work, it was shown that the strain-at-break increased with silane treatment and decreased with increment of filler loading, indicating that the silane coupling agent present on the surface of BA produced a lubricating or plasticizing effect.…”
Section: Mechanical Testingmentioning
confidence: 99%
“…The reinforcing and property modification potential of micro-and nanometer-scaled BA, with and without additional surface treatment, has been already checked in various thermoplastics (e.g. [2][3][4][5][6][7][8][9][10][11][12][13]). Polyethylenes (PEs) were often modified in the past with nanofillers, like layered silicates in order to improve their mechanical, and especially barrier properties.…”
mentioning
confidence: 99%